The Effect of Educational Media Booklet on Family Knowledge About Early Stroke Detection - Intan Putri; Siti Romadoni; Imardiani (Jurnal Inspirasi Kesehatan, 2023)
Introduction: Stroke is a health problem that needs attention because stroke is the number one cause of death in the world (200 per 100,000 population in one year) and the highest cause of death in Indonesia (500,000 people with 125,000 deaths and the rest are disabled) caused by delays in stroke treatment in the prehospital phase ( 83.9%) due to lack of knowledge of the community, especially families about early detection of stroke. Steps that can be taken to increase knowledge are to conduct education using educational media, one of which is booklet media , namely media that can be used to convey information in the form of a book containing writing and pictures. Research Objectives: To determine the effect of booklet media education on family knowledge about early stroke detection. Method: This type of quantitative research uses Pre Experimental with the One Group Pre Test-Post Test approach . Sampling used a purposive sampling technique of 59 respondents, namely families with a high risk of stroke in the working area of the Nagaswidak Health Center. The study used an instrument of knowledge about early stroke detection as many as 20 questions that had been tested for validity and reliability tests at the Pembina Palembang Health Center. The data obtained were analyzed using the Wilcoxon test. Results: The results of the analysis on the knowledge variable obtained that the value of knowledge before education was a median of 11 with a minimum value of 0 and a maximum value of 18 and the value of knowledge afte r education was a median of 15 with a minimum value of 8 and a maximum value of 20. The results of data analysis with the Wilcoxon test obtained a p - value value of 0.000(<0.05). Discussion: There is an educational effect of booklet media on family knowledge about early stroke detection. Suggestions for future researchers to be able to carry out further research that focuses on the ability of families to carry out early detection of stroke with the demonstration method.